Enterovirus and parechovirus meningitis in infants younger than 90 days old in the UK and Republic of Ireland: a British Paediatric Surveillance Unit study. Issue 6 (8th December 2018) - Kadambari, Seilesh; Braccio, Serena; Ribeiro, Sonia; Allen, David J; Pebody, Richard; Brown, David; Cunney, Robert; Sharland, Mike; Ladhani, Shamez
Abstract : Objectives: This study aimed to prospectively collect detailed clinical information for all enterovirus (EV) and human parechovirus (HPeV) meningitis cases in infants aged <90 days in the UK and Ireland. Participants, design and setting: Prospective, active national surveillance during July 2014 to July 2015 through the British Paediatric Surveillance Unit. Reporting paediatricians completed questionnaires requesting information on clinical presentation, investigations, management and outcomes at hospital discharge and after 12 months. Main outcome measures: To describe the clinical burden of EV and HPeV meningitis in infants aged <90 days. Results: During the 13-month surveillance period, 703 cases (668 EV, incidence0.79/1, 000 live- births; 35 HPeV, 0.04/1, 000 live-births) were identified. The most common clinical presentations were fever (EV: 570/668(85%); HPeV: 28/35(80%)), irritability (EV: 441/668(66%); HPeV: 23/35(66%)) and reduced feeding (EV: 363/668(54%); HPeV 23/35(66%)). Features of circulatory shock were present in 27% (182/668) of EV and 43% (15/35) of HPeV cases. Overall, 11% (76/668) of EV and 23% (8/35) of HPeV cases required intensive care support. Nearly all cases (678/703, 96%) were confirmed by cerebrospinal fluid (CSF) PCR, with 52% (309/600) having normal CSF white cell count for age. Two infants with EV meningitis died (2/668, 0.3%) and four survivors (4/666, 0.6%) had long-term complications at 12 months' follow-up. Infants with HPeV meningitis survived without sequelae. Overall 189 infants had a formal hearing test and none had sensorineural hearing loss. Conclusion: The incidence of laboratory-confirmed EV/HPeV meningitis in young infants is more than twice that for bacterial meningitis. Less than 1% will develop severe neurological complications or die of their infection. Further studies are required to formally assess long-term neurodevelopmental sequelae.